Refining the link between obesity and heart failure: insights from GLP-1 receptor agonist trials and studies adopting direct adiposity measures - Nicola Riccardo Pugliese; Francesco Paneni; Domenico Tricò; Alessandra Violet Bacca; Nicolò De Biase; Hermann Dalpiaz; Alessandro Mengozzi; Agostino Virdis; Lorenzo Ghiadoni; Stefano Taddei; Reinhold Kreutz; Konstantinos Tsioufis; et al. (Cardiovascular Diabetology)
Abstract Overweight and obesity are major risk factors for heart failure (HF), contributing to its development through metabolic, neurohormonal, haemodynamic, and inflammatory alterations. While overweight/obesity increases the risk of developing HF, its impact on patient outcomes remains complex. The “obesity paradox” suggests that a higher BMI may be associated with improved survival in patients with established HF. However, recent GLP-1 receptor agonist (GLP-1 RA) trials suggest that intentional weight loss positively influences outcomes in overweight/obese patients with HF. This seemingly contradictory evidence highlights the need for a deeper understanding of the mechanisms linking adiposity to HF outcomes. A more precise characterization of adiposity phenotypes using alternative and accurate measures of pathological fat accumulation is crucial in identifying individuals who may benefit most from anti-obesity treatments. In this context, recent research underscores the role of epicardial adipose tissue (EAT) in HF pathophysiology, as it directly influences cardiac function and structure through inflammatory, metabolic, and mechanical effects. This narrative review summarises current evidence on the impact of weight loss on HF outcomes, focusing on recent GLP-1 RA trial results. Additionally, it highlights epidemiological and molecular data supporting EAT as a novel adiposity measure that might allow refining patient selection for pharmacological weight-loss treatments. Finally, it emphasizes the need for future research to identify causal pathways linking alternative measures of visceral fat accumulation to HF outcomes. These efforts will be essential in optimizing the benefits of novel weight-loss treatments, ensuring effective and individualized therapeutic strategies for overweight or obese patients with HF. Graphical abstract